The Effect of Brainstorming, Buzz group and Simulation (BBS) Methods on Self-Control in Adolescents - Nofalia, Ifa; Wibowo, Suhendra Agung; Yuswatiningsih, Endang (Babali Publisher, 2023)
Background: Adolescent self-control is the ability to regulate emotions, behaviour, and thoughts when facing challenging or difficult situations. This study aims to determine the effect of the BBS method on self-control in adolescents. Methods: This study used a quasi-experimental pre-test and post-test control design to determine the effect of the BBS method on self-control in adolescents. The population used is youth aged 15-21 years as many as 140 adolescents and the sample count is 120 the adolescent in the village of Dukuhklopo with using simple random sampling. The research instruments used were standard operating procedures for BBS and questionnaires to determine self-control abilities in adolescents. Data results has been analysed with Wilcoxon and Mann Whitney test. Results: Based on the results Wilcoxon test of intervention and control group showed that p= 0,000, this meant that there were differences in adolescent self-control before and after the intervention in the intervention group and the control group. The Mann Whitney test result the p value in the treatment group showed p= 0,021 (p <0.05), this meant that there was a difference between before and after the intervention in the treatment group. Conclusion: BBS method can be used as a way to improve self-control abilities in adolescents. This method can be used to provide nursing care to adolescents who have decreased self-control abilities, such as to increase emotional control, control deviant sexual behaviour, control promiscuity and all other forms of juvenile delinquency.